Design of anti-load perturbation flight trajectory stability controller for agricultural UAV - Wei, Xu; XianYu, Wu; Jiazhen, Liu; Yasheng, Yan (Frontiers in Plant Science, 2023)
The UAV is widely used in agricultural fields. In many cases, agricultural UAV has a load, which affects the stability of flight trajectory. In this paper, a flight dynamics model is proposed for agricultural UAV. The robust T-S fuzzy control method is applied in the attitude angle control part, and the traditional PID controller is used in the position loop control part. In the simulation environment of load change, the flight trajectory of agricultural UAV can reach certain stability when the mass change is relatively small.